Cancer incidence in people with affective disorder: nationwide cohort study in Taiwan, 1997–2010. (September 2014) - Hung, Yen-Ni; Yang, Shu-Yu; Huang, Ming-Chyi; Lung, For-Wey; Lin, Shih-Ku; Chen, Kuan-Yu; Kuo, Chian-Jue; Chen, Ying-Yeh
Abstract : Background: Cancer is a serious public health problem worldwide, and its relationship with affective disorders is not clear. Aims: To investigate alcohol- and tobacco-related cancer risk among patients with affective disorders in a large Taiwanese cohort. Method: Records of newly admitted patients with affective disorders from January 1997 through December 2002 were retrieved from the Psychiatric Inpatient Medical Claims database in Taiwan. Cancers were stratified by site and grouped into tobacco- or alcohol-related cancers. Standardised incidence ratios (SIRs) were calculated to compare the risk of cancer between those with affective disorders and the general population. Results: Some 10 207 patients with bipolar disorder and 9826 with major depression were included. The risk of cancer was higher in patients with major depression (SIR = 2.01, 95% CI 1.85–2.19) than in those with bipolar disorder (SIR 1.39, 95% CI 1.26–1.53). The elevated cancer risk among individuals ever admitted to hospital for affective disorders was more pronounced in tobacco- and/or alcohol-related cancers. Conclusions: Elevated cancer risk was found in patients who had received in-patient care for affective disorders. They require holistic approaches to lifestyle behaviours and associated cancer risks.